STRATEGI PENGEMBANGAN KAWASAN AGROPOLITAN BERBASIS PENINGKATAN DAYA SAING PRODUK AGRIBISNIS UNGGULAN - Hadi Sasana (Riset Akuntansi Keuangan, 2017)
The aims of this research are to analyze the impact of agropolitan movement to the economic activities, and to set the development strategy of agropolitan region based on improving competitiveness of the featured agribusiness product.The data that has been used were primary data and completed by secondary data. Method of analysis that has been used were Analytic Hierarchy Process(AHP). The findings of this research are: the agropolitan movement moved and increased the agribusiness activities, agroindustry and agrotourism. Agribusiness has been increasing on institution aspect, that has been running its own self before.Agrotourism was a sector that grew fastly. It was caused by Borobudur; the tourism region.The priority of development strategy on Borobudur agropolitan region were: a). the development of farming, b) product marketing, c). human resources quality development, d). infrastructure development, e).institutional establishment and institutional strengthening.